Peran Organisasi Perdagangan Dunia (WTO) dalam Menjaga Stabilitas Perdagangan Global - Suci, Sukma Nopelita; Hardianto, Kevin; Andriany, Vicky (FEB Universitas Sultan Ageng Tirtayasa, 2025)
The World Trade Organization (WTO) plays a significant role in creating stability in international trade. As an institution tasked with regulating and facilitating global trade, the WTO aims to create a transparent, fair, and open trading system for all member countries. Through various agreements, dispute resolution mechanisms, and trade policy supervision, the WTO seeks to ensure the smooth flow of goods and services in the international market. However, challenges such as the gap between developed and developing countries, digitalization, and environmental sustainability issues continue to test the relevance of this organization. This study uses a qualitative method based on literature studies to explore the role of the WTO in addressing these challenges. The results show that although the WTO has made a major contribution to strengthening global economic cooperation, further efforts are needed to ensure inclusive involvement of all member countries and adapt trade rules to current global dynamics.